2014
DOI: 10.1111/wre.12079
|View full text |Cite
|
Sign up to set email alerts
|

Sensor‐based assessment of herbicide effects

Abstract: SummaryNon-destructive assessment of herbicide effects may be able to support integrated weed management. To test whether effects of herbicides on canopy variables could be detected by sensors, two crops were used as models and treated with herbicides at BBCH 20 using a logarithmic sprayer. Twelve days after spraying at BBCH 25 and 42 days after sowing, nine sensor systems scanned a spring barley and an oilseed rape field experiment sown at different densities and sprayed with increasing field rates of glyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
17
0
4
Order By: Relevance
“…In greenhouse experiments with both species (L. multiflorum and L. rigidum), high-density plants with thinning after application or without thinning demonstrated that a higher herbicide dose was required to obtain the same level of control of low-density plants. This can be verified by Several studies from the literature have shown that increasing the plant density affects herbicide effectiveness (Lati et al, 2012;Moon et al, 2014;Streibig et al, 2014). The increase in the density of Echinochloa crus-galli from 12 to 48 plants m -2 required an increase in the flucetosulfuron dose from 8.7 to 20.1 g ha -1 to obtain the same degree of control (Moon et al, 2014).…”
mentioning
confidence: 64%
“…In greenhouse experiments with both species (L. multiflorum and L. rigidum), high-density plants with thinning after application or without thinning demonstrated that a higher herbicide dose was required to obtain the same level of control of low-density plants. This can be verified by Several studies from the literature have shown that increasing the plant density affects herbicide effectiveness (Lati et al, 2012;Moon et al, 2014;Streibig et al, 2014). The increase in the density of Echinochloa crus-galli from 12 to 48 plants m -2 required an increase in the flucetosulfuron dose from 8.7 to 20.1 g ha -1 to obtain the same degree of control (Moon et al, 2014).…”
mentioning
confidence: 64%
“…At 23 DAT a DJI‐Phantom 3 professional UAV flew at an altitude of 40 m to capture RGB images of the whole experiment at each location. Each subplot was cropped from the images, and the Excess Green Index (2 x G–B–R) assessed for each of approximately 1850 pixel columns per sprayed plot . At the conventional field, we excluded the sprayed no‐crop plots as they did not show any better dose–response relationship.…”
Section: Methodsmentioning
confidence: 99%
“…We used the Excess Green Index for herbicides other than carotenoid inhibitors where the symptoms resulted in color changes. 5 Numerous image analyses tools have been published and made available (approximately 150) on the Internet, most of them gratis, but as Lobet 16 puts it ' … there is a lack of wileyonlinelibrary.com/journal/ps robust validation practices or the absence of longtime support'. Consequently, we do not claim that the Excess Green Index is superior to other indices 5 , but it is simple and seems rather robust.…”
Section: Excess Green Indexmentioning
confidence: 99%
See 2 more Smart Citations